2021
DOI: 10.15244/pjoes/123921
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Valent Iron Nanoparticles and Its Combined Process for Diclofenac Degradation under Various Experimental Conditions

Abstract: The use of nanoscale zero-valent iron (nZVI) for the purification of contaminated water and soil was investigated for its high potential to remove subsurface contaminants. In this study, the mechanism of diclofenac (DCF) degradation by nZVI and the combined process of nZVI and hydrogen peroxide (H 2 O 2) are discussed. The results demonstrated that nZVI with acidic conditions had a certain degradation efficiency on DCF, with a removal rate about 30% in a 2-hour reaction at pH 5. The combined process of nZVI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Other mechanisms of adsorption, such as hydrophobic interactions, π-cation interaction, and hydrogen bonding in combination with Fenton reactions in the presence of oxygen and nZVI may be also responsible for the removal rates obtained. For DCF in particular, which has a chlorinated ring, reductive dichlorination can take place via the transfer of electrons from the nZVI surface [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms of adsorption, such as hydrophobic interactions, π-cation interaction, and hydrogen bonding in combination with Fenton reactions in the presence of oxygen and nZVI may be also responsible for the removal rates obtained. For DCF in particular, which has a chlorinated ring, reductive dichlorination can take place via the transfer of electrons from the nZVI surface [87].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al [44], who investigated the performance of both H 2 O 2 and PS combined with nZVI, suggested this as a more economically sustainable method to remove pharmaceuticals from water. Furthermore, Liang et al [87] demonstrated the improved removal efficiency of DCF when nZVI was combined with H 2 O 2 . Therefore, this practice may offer a promising method for treating recalcitrant pharmaceutical compounds at trace-level concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The disclosure of the problem initiated a number of scientific studies focused on finding technical and material solutions to increase the effectiveness of pharmaceuticals that resistant to degradation [ 40 , 41 ]. The most frequently mentioned alternatives are adsorption [ 42 , 43 , 44 ], membrane separation [ 45 , 46 , 47 ], and advanced oxidation processes [ 48 , 49 , 50 ], as well as hybrid methods [ 51 ]. Currently, the highest removal efficiency is achieved by ozonation processes and treatment with activated carbon [ 52 ].…”
Section: Introductionmentioning
confidence: 99%